A noção de festa nas relações públicas: a comunicação comunitária na Feira da Vila Madalena - Freire, Iraê Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This paper aims to review the concept of Festival in the area of Public Relations and discuss about it according to the Classical Anthropology, Urban Anthropology and Public Relations theories, by their main exponents Emile Durkhein, Rita Amaral, Roberto Damatta and Joseph Guilherme Magnani, Waldemar Kunsch, Margarida Kunsch, Cicilia Peruzzo, Rennan Mafra and Márcio Simeone. The 33rd Vila Madalena Fair, a craft fair that takes place once a year in São Paulo, was chosen as a case study to provide this research with an empirical dimension. The Fair emerged as a result of the neighborhood residents and merchants´ mobilization in the late 70's and until today, has been responsible for the re-updating and the strengthening of the neighborhood identity. Thus, the proposal is to evaluate the possibilities of the Festival performance as a favorable strategy to sociability, to the strengthening and the re-updating the symbolic representations of a community

Este trabalho tem como objetivo rever o conceito de Festa na área de Relações Públicas e problematizá-lo com base nas teorias da Antropologia Clássica, da Antropologia Urbana e das Relações Públicas, que contam entre seus principais expoentes Émile Durkhein, Rita Amaral, Roberto DaMatta e José Guilherme Magnani, Waldemar Kunsch, Margarida Kunsch, Cicília Peruzzo, Rennan Mafra e Márcio Simeone. Para que essa pesquisa ganhasse uma dimensão empírica, foi escolhida como estudo de caso a 33ª Feira da Vila Madalena, feira de artesanato que ocorre uma vez por ano, na cidade de São Paulo. A Feira surgiu como resultado da mobilização dos moradores e comerciantes do bairro no final da década de 70 e ainda hoje é responsável por re-atualizar e reforçar a identidade do bairro. Assim, a proposta deste trabalho é avaliar as possibilidades da atuação da Festa como estratégia favorável à sociabilidade, ao reforço e re-atualização das representações simbólicas de uma comunidade
Keywords: Festas populares; Relações publicas; Artesanato - Exposições; Identidade social; Parties; Public relations; Handicraft; Exhibitions; Group identity